Aptamer-conjugated theranostic hybrid graphene oxide with highly selective biosensing and combined therapy capability. (3rd October 2014) - Viraka Nellore, Bhanu Priya; Pramanik, Avijit; Chavva, Suhash Reddy; Sinha, Sudarson Sekhar; Robinson, Christen; Fan, Zhen; Kanchanapally, Rajashekhar; Grennell, Justin; Weaver, Ivy; Hamme, Ashton T.; Ray, Paresh Chandra
Abstract : Cancer is a life-threatening disease, which is rapidly becoming a global pandemic. Driven by this need, here we report for the first time an aptamer-conjugated theranostic magnetic hybrid graphene oxide-based assay for highly sensitive tumor cell detection from blood samples with combined therapy capability. AGE-aptamer-conjugated theranostic magnetic nanoparticle-attached hybrid graphene oxide was developed for highly selective detection of tumor cells from infected blood samples. Experimental data indicate that hybrid graphene can be used as a multicolor luminescence platform for selective imaging of G361 human malignant melanoma cancer cells. The reported results have also shown that indocyanine green (ICG)-bound AGE-aptamer-attached hybrid graphene oxide is capable of combined synergistic photothermal and photodynamic treatment of cancer. Targeted combined therapeutic treatment using 785 nm near-infrared (NIR) light indicates that the multimodal therapeutic treatment is highly effective for malignant melanoma cancer therapy. The reported data show that this aptamer-conjugated theranostic graphene oxide-based assay has exciting potential for improving cancer diagnosis and treatment.